2019
DOI: 10.1176/appi.ps.201800322
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Use of Mental Health and Substance Use Treatment Services by Justice-Involved Youths

Abstract: Objective: Nonincarcerated (community-supervised) youths who are first-time offenders have high rates of mental and substance use disorders. However, little is known about their use of psychiatric services (mental health and substance use) or factors associated with service use. This study examined the prevalence, determinants, and barriers to service use among community-supervised youths.Methods: Data were from a longitudinal study of mental health and substance use outcomes among adolescents ages 12-18 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…In particular, digital mobile health (mHealth) technology is an efficacious, low-cost way of reaching underserved, vulnerable populations to engage them into and/or deliver quality care [19]. mHealth circumvents many barriers to treatment participation reported by caregivers of justice-involved youth [20], allowing for instantaneous, portable access and direct communication with providers [21]. mHealth effectively increases patient communication, monitoring, and education to reduce the burden of diseases associated with poverty and improves access to health services, clinical diagnosis, and treatment adherence [22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, digital mobile health (mHealth) technology is an efficacious, low-cost way of reaching underserved, vulnerable populations to engage them into and/or deliver quality care [19]. mHealth circumvents many barriers to treatment participation reported by caregivers of justice-involved youth [20], allowing for instantaneous, portable access and direct communication with providers [21]. mHealth effectively increases patient communication, monitoring, and education to reduce the burden of diseases associated with poverty and improves access to health services, clinical diagnosis, and treatment adherence [22].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that screening approaches and thresholds adopted for the broader population of CWS-involved youth may be directly applicable to youth impacted by CSE. Yet, despite the high levels of substance use among our sample, the prevalence of substance use treatment was only 40%, underscoring the gap between treatment need and treatment receipt among youth impacted by CSE (Yonek et al 2019). Accordingly, increasing linkages to substance use prevention and treatment services and interagency collaboration among systems of care are essential to facilitating access to needed services for youth impacted by CSE (Howell et al 2004;Chuang and Wells 2010).…”
Section: Recognizing the High Burden Of Substance Use Among Sexually mentioning
confidence: 83%
“…Prior research has also shown that acculturation gaps are associated with higher levels of family stress and dysfunction, poor communication, and risk behaviors such as substance use in adolescents (Martinez, 2006). For FTO-CINI adolescents in particular, behaviors like substance use have been shown to elevate risk for other psychiatric symptoms such as depression, anxiety, and suicidal ideation and increase risk for recidivism and justice involvement, particularly if unassessed and unaddressed (Yonek et al, 2019). Understanding the acculturation gap’s role in Latinx families with justice-involved adolescents seems critical given that previous studies have shown that integrating immigration and culture-specific components in interventions improves treatment (Griner & Smith, 2006; Parra-Cardona et al, 2019).…”
Section: Discussionmentioning
confidence: 99%